2017
DOI: 10.1073/pnas.1703939114
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of PDE-regulated phosphoproteomes reveal unique and specific cAMP-signaling modules in T cells

Abstract: Specific functions for different cyclic nucleotide phosphodiesterases (PDEs) have not yet been identified in most cell types. Conventional approaches to study PDE function typically rely on measurements of global cAMP, general increases in cAMP-dependent protein kinase (PKA), or the activity of exchange protein activated by cAMP (EPAC). Although newer approaches using subcellularly targeted FRET reporter sensors have helped define more compartmentalized regulation of cAMP, PKA, and EPAC, they have limited abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 90 publications
0
31
0
Order By: Relevance
“…This analysis revealed clusters of interacting proteins associated with particular cell pathways, which differed between the PDE3 and -4 and the PDE1, -7, and -8 inhibitor treatment groups. Finally, Beltejar et This study by Beltejar et al (16) has important clinical implications. Because so many fundamental physiological processes are regulated by cAMP signaling, PDE inhibitors are under intense development for a whole host of disorders and are seeing increasing approval for clinical use.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…This analysis revealed clusters of interacting proteins associated with particular cell pathways, which differed between the PDE3 and -4 and the PDE1, -7, and -8 inhibitor treatment groups. Finally, Beltejar et This study by Beltejar et al (16) has important clinical implications. Because so many fundamental physiological processes are regulated by cAMP signaling, PDE inhibitors are under intense development for a whole host of disorders and are seeing increasing approval for clinical use.…”
mentioning
confidence: 83%
“…Although the use of subcellularly targeted FRET reporter sensors have helped to confirm the role of PDEs in regulating the temporal and spatial control of cAMP during signal transduction, this approach only has limited ability to link specific PDEs to regulation of downstream effector molecules and biological functions. In PNAS, Beltejar et al (16) use mass spectrometry coupled with the use of specific isozyme-selective PDE inhibitors to characterize, for the first time, the phosphoproteomes of functional pools of cAMP regulated by specific PDEs, to delineate which PDEs control phosphorylation of which proteins, leading to regulation of different responses by different PDEs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm the downstream effects and map out the proteins targeted by PKA activation, identification of cAMP-dependent phosphorylation sites is key. Phosphoproteomics can help link this cAMPmediated PKA regulation to downstream effector molecules and biological functions (Beltejar et al, 2017). Mass spectrometry can identify thousands of phosphosites with high precision (Altelaar et al, 2013) and quantitative mass spectrometry has been shown to be sensitive to dynamic changes in protein phosphorylation following GPCR activation (Williams et al, 2016).…”
Section: Using Phosphoproteomics To Define Camp Signalling Domainsmentioning
confidence: 99%